Water Deficit as a Security Threat - Sakson-Boulet, Anna (Przegląd Strategiczny, 2016)
The aim of the article is to explain the key definitions connected with water security and to analyse state relations in the context of water issues. In this context therefore water can be seen to be a precious resource because there it has no substitute. Thus the lack of water security is emerging as one of the major barriers for economic and social growth in developing countries and a source of domestic conflicts. On the other hand, water-related events might result in international cooperation, as Kofi Annan noticed during the celebration of World Water Day: “Fierce national competition over water resources has prompted fears that water issues contain the seeds of violent conflict. [...] If all world’s peoples work together, a secure and sustainable water future can be ours”. What is certain, in the near future any environmental security planning will have to take into consideration the prime issue of water security.